2017
DOI: 10.1097/j.pain.0000000000000859
|View full text |Cite
|
Sign up to set email alerts
|

Does expecting more pain make it more intense? Factors associated with the first week pain trajectories after breast cancer surgery

Abstract: We studied postoperative pain trajectories and associated factors. Expectation of severe postoperative pain was associated with higher intensity of experimental and postoperative pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
44
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 51 publications
(71 reference statements)
5
44
1
1
Order By: Relevance
“…Fletcher et al [6] have reported an incidence of moderate to severe CPOP of 11.8% at 1 year after surgery whereas Haroutiunian et al [7] reported the incidence of 6-68% for postoperative neuropathic pain depending on the type of surgery. Several risk factors are associated with the development of CPOP such as preoperative pain, type of surgery, perioperative nerve injury, fear of surgery, pain catastrophizing, anxiety, expectation of pain, obesity, young age and sex (female) [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Fletcher et al [6] have reported an incidence of moderate to severe CPOP of 11.8% at 1 year after surgery whereas Haroutiunian et al [7] reported the incidence of 6-68% for postoperative neuropathic pain depending on the type of surgery. Several risk factors are associated with the development of CPOP such as preoperative pain, type of surgery, perioperative nerve injury, fear of surgery, pain catastrophizing, anxiety, expectation of pain, obesity, young age and sex (female) [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study in 563 women having breast cancer surgery, Sipilä and colleagues [21] found that patient's expectations of severe postoperative pain were associated with higher clinical pain intensity and increased initial oxycodone use at the PACU. In contrast, in another and smaller prospective study [10] investigating patients' ability to forecast their disability and pain two weeks after hand surgery, only weak correlations between forecasted and realized pain was discovered [10].…”
Section: Discussionmentioning
confidence: 99%
“…Several perioperative factors such as age, catastrophizing pain scores, gender, and psychological distress have been suggested to be closely associated with patient pain perception before operations [9][10][11]. Preoperative expectations of pain may also affect the severity of postoperative pain [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%